A review of circular economy opportunities in the mining sector - S. Khan; F. Magweregwede (The Southern African Institute of Mining and Metallurgy, 2025)
Circular economy opportunities for the mining sector are presented in this paper. A literature review was undertaken, followed by qualitative data gathering through survey questionnaires and unstructured interviews, and stakeholder engagements through workshops. The circular economy opportunities were identified and categorised according to the three circular economy principles of designing out waste and pollution, keeping products and materials in use, and regenerating natural systems. Opportunities aligned with the first principle include increased ore extraction efficiency processes, water recovery and recycling, substitution of raw materials, technology and waste utilisation for carbon capture and biotechnology. The second principle includes opportunities such as zero waste-to-landfill strategies, repurposing of mine waste, re-mining of tailings, recycling metals and processing of residues, and urban mining of electronic waste. Opportunities aligned with the third principle include the adoption of renewable energy, green hydrogen production, repurposing of post mining landscapes, and eradication of alien invasive vegetation. Furthermore, the challenges of implementing circular economy in the mining sector are discussed. The current rate of waste generation from mining activities far exceeds the rate of reuse and repurposing. Recycling of large tyres and characterisation of hazardous electronic waste also pose challenges. The most implementable circular economy opportunities in the mining sector are those aligned with the second principle of keeping materials in use. The high impact opportunities aligned with the first principle of designing out waste and pollution, and the third principle of regenerating natural systems, are more difficult to implement as they require large investments.